ANALISIS PENGARUH TINGKAT SUKU BUNGA SBI DAN VOLUME EKSPOR IMPOR TERHADAP NILAI TUKAR RUPIAH - Yudha, Andy El; Hadi, Syamsul (Jurnal Ekonomi Pembangunan, 2009)
The purpose of this research is to know the level of effect interest rate and volume export import to year rupiah exchange rate 2002-2006. In this research, the auther taken hypothesis which guesses that interest rate, value export import, rupiah exchange rate to $ US Lag_1 has significant effect to rupiah exchange rate. Technique analyse the data by writer by using doubled linear analysis regresi with the ordinary smallest square (OLS) and also use the test t and test F. From the analysis can be pulled conclusion that variable interest rate and export import volume have negative effect to rupiah exchange rate, while variable rupiah exchange rate to $ US Lag_1 have positive and significant to rupiah exchange rate.